Transcranial Focused Ultrasound in Functional Neurosurgery for Essential Tremor and Parkinson’s Disease: A Review Article - Azimi, Parisa (International Clinical Neuroscience Journal, 2016)
PURPOSE: Transcranial magnetic resonance guided focused ultrasound (MRgFUS) is a new development in the field of functional neurosurgery. A comprehensive review of the current literature was performed to evaluate of transcranial MRgFUS in treatment of essential tremor (ET) and Parkinson’s disease. METHODS: Articles available in electronic databases of PubMed, and Web of Science, as of July 2016 were reviewed. The strategy included a combination of key words ’MRgFUS’, ’tremor’, ’Parkinson’, ’brain’, ’ head ’, ’tumor’, ’transcranial’ and ’focused ultrasound’ in the title and abstract of the manuscripts. In addition transcranial MRgFUS systems and cost-effectiveness of treatment were assessed. Finally, the major findings are summarized. RESULTS: Fifty-eight articles met the inclusion criteria for review. Among these, 15 studies eligible for inclusion in this review. The synthesis of the data demonstrated that, transcranial MRgFUS have been successfully used for treatment of essential tremor and Parkinson’s disease. Lesions were created under real-time MRI guidance, with peak temperatures of between 52° C and 63° C. Adverse events during transcranial MRgFUS reported such as headache, dizziness, vertigo, lip paresthesia, and hypogeusia. However, there were no significant treatment-related complications or side effects. At present, one of the limitations of transcranial MRgFUS is high price of treatment. However, continued advances in technology can be expected to further refine the high price market of transcranial MRgFUS. CONCLUSION: The findings showed that essential tremor and Parkinson’s disease can be effectively treated with transcranial MRgFUS method. Long-term clinical data are forthcoming.